2020
DOI: 10.1038/s41370-020-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and exposures of graphene nanomaterials, titanium dioxide nanofibers, and nanoparticles during down-stream industrial handling

Abstract: Today, engineered nanomaterials are frequently used. Nanosized titanium dioxide (TiO 2) has been extensively used for many years and graphene is one type of emerging nanomaterial. Occupational airborne exposures to engineered nanomaterials are important to ensure safe workplaces and to extend the information needed for complete risk assessments. The main aim of this study was to characterize workplace emissions and exposure of graphene nanoplatelets, graphene oxide, TiO 2 nanofibers (NFs) and nanoparticles (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 66 publications
3
16
0
Order By: Relevance
“…Even though CNT powder was handled openly in the chemical and manufacturing laboratories, surface contamination could only be detected on one surface (a door handle on the corridor side) outside these laboratories. The percentage of surface samples with CNT contamination was in the same range as reported by Lovén et al (2021) , in which TiO 2 nanofibres were tape sampled, but lower than reported in a previous study of CNTs ( Hedmer et al , 2015 ). The detected surface contamination could most likely be related to the different production steps of the nanocomposite as most of the contaminated surfaces were found in the near-field zone in the chemical and manufacturing laboratories, where the WTs were performed.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Even though CNT powder was handled openly in the chemical and manufacturing laboratories, surface contamination could only be detected on one surface (a door handle on the corridor side) outside these laboratories. The percentage of surface samples with CNT contamination was in the same range as reported by Lovén et al (2021) , in which TiO 2 nanofibres were tape sampled, but lower than reported in a previous study of CNTs ( Hedmer et al , 2015 ). The detected surface contamination could most likely be related to the different production steps of the nanocomposite as most of the contaminated surfaces were found in the near-field zone in the chemical and manufacturing laboratories, where the WTs were performed.…”
Section: Discussionsupporting
confidence: 73%
“…The method was modified with an extended oxidation time at the highest temperature in order to achieve complete oxidation of all carbonaceous nanomaterials. Further details of the analytical procedure are given elsewhere ( Hedmer et al , 2014 ; Lovén et al , 2021 ). The limit of detection (LOD) of the method for EC is 0.06 µg C cm −2 , corresponding to 0.6 and 0.5 µg C m −3 for a 4-h sample for the respirable and inhalable fraction, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), we evaluated the potential genotoxicity of GO sheets after single (30 µg) or repeated (3 × 1 µg or 3 × 10 µg) pulmonary exposure. The low dose of 3 × 1 µg represented a realistic dose of exposure at the workplace when limited mitigating measures are applied, whereas 30 µg (or 3 × 10 µg) was used here as worst-case exposure scenario (accident) that may happen during specific tasks such as dry powder handling without protective measures [ 39 , 40 ]. The aim was to compare outcomes from standard exposure protocol (i.e., single exposure triggering acute response) to outcomes from chronic exposure that may better represent exposure at the workplace [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…EC can also be estimated as equivalent black carbon (eBC) (Cai et al 2014 ; Yu et al 2015 ) and measured with direct-reading instruments. This enables the identification of high-exposure work tasks (Lovén et al 2020 ) that are not resolved with the time-integrated EC measurement. However, to the best of the authors’ knowledge, no studies of time-resolved personal exposure to eBC during underground mining have previously been published.…”
Section: Introductionmentioning
confidence: 99%